PREVALENSI KOMPLIKASI KARDIOVASKULER PADA PASIEN DIABETES MILITUS DI DENPASAR - Tarigan, Robby Paguh (E-Jurnal Medika Udayana; vol 5 no 2(2016):e-jurnal medika udayana, 2016)
PREVALENCE OF CARDIOVASCULAR COMPLICATIONS IN DIABETES MILITUS PATIENTS AT DENPASAR The alteration of human life to modern lifestlyle had influenced many developing countries, included Indonesia. Beside it took positive effects, it also took some negatif effects, and on of it was increasing the case of degenerative disease, included the case of Diabetes Militus (DM). One of the DM complication that had a high number of morbidity and mortality is cardiovasculer complication. The purpose of this research is to observe the prevealance of cardiovascular complication among DM patient and the influence of glikemic control and risk factors that induce complication occured. The sample were collected from DM patients who joined to world diabetic celebration in 24 November 2013 that qualify including and excluding criteria. 41 samples are collected, 23 man and 18 woman. The average age is 60,78 years old. Data were collected based on measuring of BMI, random blood glucose, and quisoner. The result, 20 samples had got cardiovaskuler disease. When it was grouped, 3 cases were got before DM and 17 cases were got after DM. From 17 cases, it was found 14 cases of heart disease & hipertention,  and 13 cases of angina.
Keywords: Diabetes Militus; Prevealence of Cardiovaskuler Complication; The influence of glikemic control and risk factors